Estudio electrofisiologico en la neuropatia por Vincristina Vincristine neuropathy: an electrophysiological study - Olga P. Sanz; A. Colombi; M. Somoza; D. Monteverde (Arquivos de Neuro-Psiquiatria)
Diez pacientes afectados por diversas patologías que requerían tratamiento crónico con Vincristina, fueron sometidos a estudios electrofisiológicos en los que se valoró: el número de unidades motoras (UM) funcionantes en los músculos de la eminencia tenar, los valores de los incrementos medios de UM, velocidad de conducción motora y su latencia residual en el nervio mediano, la velocidad de conducción sensitiva del mismo nervio y el estado de la transmisión neuromuscular. Los valores obtenidos fueron comparados con grupos controles. Los resultados mostraron disminución del número de UM; las UM remanentes presentaron amplitud reducida junto a otras cuyo tamaño no superaba el del grupo control, hecho que sugiere la incapacidad de lograr una reinervación adecuada. Las velocidades de conducción motora y sensitiva mostraron valores diminuídos, con mayor compromiso en los segmentos distales. Junto a estos datos se halló respuesta miasteniforme al estímulo repetitivo. Todos estos resultados permiten postular la existencia de un compromiso de la unidad motora, abarcando todos sus segmentos, en pacientes intoxicados con Vincristina. Ten patients treated with vincristine were submitted for electrophysiological examination. It was investigated the number of motor units within the thenar muscle following a technique described previously (Sica et al. — 1974); motor and sensitive conduction velocities as well as motor distal latencies in the median nerve were studied following conventional techniques. The behaviour of the evoked muscle potential with repetitive supramaximal stimulation over the median nerve was also investigated. The findings were compared with control groups. The estimated number of motor units was disminished in eight of ten patients and the average number was significantly different from the control group (control 318 ± 71 UM; patients 174 ± 84 UM; P < 0.001). The potential amplitudes in most of the surviving units were reduced, others remaining within the normal range. This makes apparent that the peripherical nervous system fails to compensate adequatly and, furthermore, a loss of individual muscle fibres occurs within some individual units. The conduction velocities of the fastest conducting motor nerve fibres were reduced and motor distal latencies prolongued (Table 1). Maximal impulse conduction velocities were measured in sensory fibres. In 5 of 7 subjets investigated the values laied just beyond the lower limit of the normal range. The amplitude of the sensory orthodromic evoked potential in the median nerve at the wrist was disminished almost in the whole group. The decremental muscle response to repetitive nerve stimulation, can be interpreted as the result of the damage at the neural apparatus at the motor end plate; it was observed in 57% of the patients. In summary, evidences have been registered showing that the nervous supply to the muscle is affected in patients treated with vincristine; the motor unit behaviour under this conditions is discussed.